MDMA-assisted therapy is associated with a reduction in chronic pain among people with post-traumatic stress disorder - Christie, Devon; Yazar-Klosinski, Berra; Nosova, Ekaterina; Kryskow, Pam; Siu, Will; Lessor, Danielle; Argento, Elena (Frontiers in Psychiatry, 2022)
Introduction: Increasing evidence demonstrates 3,4-methylenedioxymethamphetamine (MDMA)-assisted therapy (MDMA-AT) is a safe and effective treatment for post-traumatic stress disorder (PTSD). There is growing interest in MDMA-AT to address a range of other health challenges. Chronic pain and PTSD are frequently comorbid, reciprocally independent conditions, though the possible role of MDMA-AT in treating chronic pain remains under-investigated. The present analysis examined the impact of manualized MDMA-AT on chronic pain severity among participants with post-traumatic stress disorder (PTSD) who were enrolled in Phase 2 FDA clinical trials investigating MDMA-AT for PTSD. Materials and Methods: Data (December 2017 – August 2019) from a subset of participants (n=32) were accessed by permission from the Multidisciplinary Association for Psychedelic Studies Public Benefit Corporation (MAPS PBC), who sponsored the original Phase 2 open-label study. Multivariable analysis of variance (ANOVA) was utilized to compare pre- versus post-treatment Chronic Pain Grade (CPG) values, adjusting for demographics (age, sex, and ethnicity). K-means clustering was then used to group the sample into three clusters to denote high (n=9), medium (n=11), and low (n=12) baseline pain, and the same analysis was repeated for each cluster. Results: Among the 32 participants included in this analysis, 59% (n=19) were women, 72% (n=23) were white, and median age was 38 (interquartile range [IQR]=31-47). Overall, 84% (n=27) reported chronic pain, and 75% (n=24) reported disability associated with chronic pain. Significant reductions in CPG subscales for Pain Intensity and Disability Score, and overall CPG Severity Grade were observed among participants in the highest pain cluster (n=9, p<0.05) post- versus pre-treatment. Discussion: Findings demonstrate a high prevalence of chronic pain in this sample of people with severe PTSD and that chronic pain scores among those reporting the highest pain were significantly lower following MDMA-AT. While these data are limited, when considered alongside the frequency of comorbid chronic pain and PTSD and promising efficacy of MDMA-AT for treating PTSD, these findings encourage further research exploring the role of MDMA-AT for chronic pain.